What Leads to Prosocial Behaviors on Social Networking Services: A Tripartite Model. Issue 1 (2nd January 2017) - Kuem, Jungwon; Ray, Soumya; Siponen, Mikko; Kim, Sung S.
Abstract: The major challenge for social networking services (SNS) has been in getting users to exhibit prosocial behavior by active participation in creating and sharing content. We seek to integrate and reconcile the varying, and sometimes conflicting, explanations of prosocial behaviors at SNS. Rooted in postadoption behavior and commitment theory, our study offers three distinct mechanisms that regulate how one's experience at an SNS translates into commitment that leads to prosocial behavior. In particular, satisfaction, affective commitment, and active participation substantiate a dedication-based mechanism; past investments, continuance commitment, and resulting inattention to alternatives form a constraint-based mechanism; and social support, normative commitment and users' intentions to moderate comments are a third, obligation-based mechanism. We empirically tested this tripartite model against data collected from actual Facebook users. The results of our analysis supported the proposed relationships between each mechanism's experiential factor, mediating type of commitment, and prosocial outcome. Intermechanism effects were rare between commitment mediators and outcomes, they were common between experiential antecedents and commitment factors. Understanding these mechanisms allows SNS managers to fine-tune their service experience to promote specific prosocial behaviors. Meanwhile, researchers benefit from our overarching view of prosocial behavior at SNS that helps to combine and contrast emergent perspectives and theories.